Comparable or higher prevalence of comorbidities in antiphospholipid syndrome vs rheumatoid arthritis: a multicenter, case-control study. (29th June 2020) - Panopoulos, Stylianos; Thomas, Konstantinos; Georgiopoulos, Georgios; Boumpas, Dimitrios; Katsiari, Christina; Bertsias, George; Drosos, Alexandros A; Boki, Kyriaki; Dimitroulas, Theodoros; Garyfallos, Alexandros; Papagoras, Charalampos; Katsimbri, Pelagia; et al.
Abstract: Objectives: Evidence on comorbidity prevalence in antiphospholipid syndrome (APS) and its difference from high comorbidity burden rheumatic diseases is limited. Herein, we compare multiple comorbidities between APS and RA. Methods: A total of 326 patients from the Greek APS registry [237 women, mean age 48.7 (13.4) years, 161 primary APS (PAPS), 165 SLE-APS] were age/sex matched (1:2 ratio) with 652 patients from a Greek multicentre RA cohort of 3115 patients. Prevalence of cardiovascular (CV) risk factors, stroke, coronary artery disease (CAD), osteoporosis, diabetes mellitus (DM), chronic obstructive pulmonary disease (COPD), depression and neoplasms were compared between APS and RA patients using multivariate regression analysis. Results: Ηyperlipidemia and obesity (ΒΜΙ ≥ 30 kg/m 2 ) were comparable while hypertension, smoking, stroke and CAD were more prevalent in APS compared with RA patients. Osteoporosis and depression were more frequent in APS, while DM, COPD and neoplasms did not differ between the two groups. Comparison of APS subgroups to 1:2 matched RA patients revealed that smoking and stroke were more prevalent in both PAPS and SLE-APS vs RA. Hypertension, CAD and osteoporosis were more frequent only in SLE-APS vs RA, whereas DM was less prevalent in PAPS vs RA. Hyperlipidaemia was independently associated with CV events (combined stroke and CAD) in PAPS and SLE-APS, while CS duration was associated with osteoporosis in SLE-APS. Conclusion: Comorbidity burden in APS (PAPS and SLE-APS) is comparable or higher than that in RA, entailing a high level of diligence for CV risk prevention, awareness for depression and CS exposure minimization.